2013
DOI: 10.1177/1740774513506619
|View full text |Cite
|
Sign up to set email alerts
|

Concealment and fabrication: The hidden price of payment for research participation?

Abstract: Paid participation in clinical research has been common and controversial for years. Discussion in scholarly literature, in guidance and regulatory documents, and among investigators and institutional review board members has centered around concerns about impairing judgment, blinding subjects to risk, exploitation, commodification, or unjust distribution of research burden [1]. The article by Devine et al. [2] in this issue addresses a different and largely understudied concern -the potential for paid researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…For example, some volunteers simultaneously participate in studies as depressed patients and HVs (28, 29) as there are no objective tests to diagnose depression or to prove mental health. Although there is no data on the prevalence of deception in psychiatric research, its negative impact on research integrity has recently gained more attention (6, 11, 28, 29). …”
Section: Discussionmentioning
confidence: 99%
“…For example, some volunteers simultaneously participate in studies as depressed patients and HVs (28, 29) as there are no objective tests to diagnose depression or to prove mental health. Although there is no data on the prevalence of deception in psychiatric research, its negative impact on research integrity has recently gained more attention (6, 11, 28, 29). …”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is no centralized registry of research participants, which means that healthy volunteers can easily circumvent restrictions that could otherwise limit their trial participation. 1315 Compensation for these trials varies dramatically based on the overall length of the trial, number of days confined to the research facility, and number of outpatient visits. The average US phase I trial typically pays between $2000 and $4000.…”
Section: Introductionmentioning
confidence: 99%
“…Some scholars argue that moderate payments do not negatively affect research participants (Halpern, Karlawish, Casarett, Berlin, & Asch, 2004), but many others argue that financial compensation, particularly in the case of vulnerable research populations, can unduly influence them to choose to participate (Gelinas et al, 2018; Largent, Grady, Miller, & Wertheimer, 2013; Wong & Bernstein, 2011). Some caution that financial compensation effectively restricts research participants’ ability to provide free, uncoerced, and informed consent (Grady, 2001) and prompts participants to minimize or neglect risk taking (Bentley & Thacker, 2004; Macklin, 1981) or to engage in deception (Devine et al, 2015; Dickert, 2013) Table 1 provides a summary description of the mainthemes that emerged during the analysis. In the area of substance abuse research, some have suggested that financial compensation raises ethical questions because research participants might use financial compensation to acquire drugs (Brody & Waldron, 2000; Koocher, 1991).…”
mentioning
confidence: 99%